Integrated Ethnoscience Barcode Quartet Card Media: A Solution to Optimize Student Science Literacy - Alviani, Badra Intan Mei; Sayekti, Ika Candra (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to develop and analyze the feasibility of learning media in the form of ethnoscience-integrated barcoded quartet cards to optimize the science literacy of grade IV elementary school students. Methodology: This research employed Research and Development (R&D) using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation), limited to the media development stage. Data were collected through interviews, observations, questionnaires, and validation sheets. Results: The results showed that: (1) the developed product is a science learning media in the form of barcoded quartet cards integrated with ethnoscience, containing material about changes in the state of matter; (2) the feasibility tests of the media and material gained scores of 95.59% and 95%, respectively, indicating that the media is highly feasible. Applications/Originality/Value: The originality of this media lies in its integration of ethnoscience—local wisdom related to changes in the state of matter—into interactive learning tools to enhance the science literacy of fourth-grade elementary students.